Screening of thermotolerant and thermophilic fungi aiming β-xylosidase and arabinanase production - Benassi,Vivian Machado (2014)
Plant cell wall is mainly composed by cellulose, hemicellulose and lignin. The heterogeneous structure and composition of the hemicellulose are key impediments to its depolymerization and subsequent use in fermentation processes. Thus, this study aimed to perform a screening of thermophilic and thermotolerant filamentous fungi collected from different regions of the São Paulo state, and analyze the production of β-xylosidase and arabinanase at different temperatures. These enzymes are important to cell wall degradation and synthesis of end products as xylose and arabinose, respectively, which are significant sugars to fermentation and ethanol production. A total of 12 fungal species were analyzed and 9 of them grew at 45 ºC, suggesting a thermophilic or thermotolerant character. Additionally Aspergillus thermomutatus anamorph of Neosartorya and A. parasiticus grew at 50 ºC. Aspergillus niger and Aspergillus thermomutatus were the filamentous fungi with the most expressive production of β-xylosidase and arabinanase, respectively. In general for most of the tested microorganisms, β-xylosidase and arabinanase activities from mycelial extract (intracellular form) were higher in cultures grown at high temperatures (35-40 ºC), while the correspondent extracellular activities were favorably secreted from cultures at 30 ºC. This study contributes to catalogue isolated fungi of the state of São Paulo, and these findings could be promising sources for thermophilic and thermotolerant microorganisms, which are industrially important due to their enzymes.